Safety of transient elastography in patients with implanted cardiac rhythm devices. Issue 3 (March 2017) - Friedrich-Rust, Mireen; Schoelzel, Fabian; Linzbach, Sven; Bojunga, Joerg; Zeuzem, Stefan; Seeger, Florian
Abstract: Background: At present the use of transient elastography (TE) in patients with pacemaker (PM) or implantable cardioverter defibrillator (ICD) devices is not recommended, since the safety due to the electromagnet embarked in the vibrator for producing the shearwave has not been evaluated. However, no adverse events of sonographic examinations in this patient group have been reported. Aims: The aim of the present study was to evaluate the safety of TE in patients with PM or ICD. Methods: In a prospective study we evaluated safety and function of such devices during TE. In 17 patients with PM and 17 patients with ICD, the function of the device was checked prior to and after TE examination. Results: In none of the 34 patients changes in stimulation thresholds, electrode impedance and sensing were detected. Conclusion: Our findings support the assumption that the potential harm of TE in patients with PM and ICD is rare.